The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.3109/10408444.2011.623149
|View full text |Cite
|
Sign up to set email alerts
|

Toxicological review and oral risk assessment of terephthalic acid (TPA) and its esters: A category approach

Abstract: Polyethylene terephthalate, a copolymer of terephthalic acid (TPA) or dimethyl terephthalate (DMT) with ethylene glycol, has food, beverage, and drinking water contact applications. Di-2-ethylhexyl terephthalate (DEHT) is a plasticizer in food and drinking water contact materials. Oral reference doses (RfDs) and total allowable concentrations (TACs) in drinking water were derived for TPA, DMT, and DEHT. Category RfD and TAC levels were also established for nine C(1)-C(8) terephthalate esters. The mode of actio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(39 citation statements)
references
References 96 publications
0
37
0
Order By: Relevance
“…For example, chronic dietary exposure caused general toxicity in rats (Ball et al 2012). Female Sprague–Dawley rats administered DEHTP in the diet for 90 days showed no major organ or systemic toxicity at 0.5% (v/v) dose levels, but some effects on hematology parameters and increase in relative liver weights were observed at the 1.0% dose (Barber and Topping 1995).…”
Section: Introductionmentioning
confidence: 99%
“…For example, chronic dietary exposure caused general toxicity in rats (Ball et al 2012). Female Sprague–Dawley rats administered DEHTP in the diet for 90 days showed no major organ or systemic toxicity at 0.5% (v/v) dose levels, but some effects on hematology parameters and increase in relative liver weights were observed at the 1.0% dose (Barber and Topping 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Terephthalic acid was originally reported to be nontoxic (Hoshi et al 1968), but later studies involving higher levels of exposure to this compound suggested that it may impair testicular functions (Cui et al 2004). An extensive review on terephthalic acid has been recently published (Ball et al 2011). Although terephthalic acid has a certain resemblance in terms of molecular structure to DEHP, it cannot leach out of the final product and is chemically distinct from DEHP.…”
Section: Varieties Of Phthalates: Phthalates and Terephthalatesmentioning
confidence: 99%
“…However, as mentioned above, TPA is the primary metabolite of DMT (Heck and Kluwe, 1980; Moffitt et al, 1975) and our study shows that DMT has no endocrine activity in any of the assays performed. TPA also showed no evidence of estrogenic activity in a two-generation reproduction study (Ball et al, 2012). …”
Section: Discussionmentioning
confidence: 99%